Microbiota profiling reveals alteration of gut microbial neurotransmitters in a mouse model of autism-associated 16p11.2 microduplication - Fu, Zhang; Yang, Xiuyan; Jiang, Youheng; Mao, Xinliang; Liu, Hualin; Yang, Yanming; Chen, Jia; Chen, Zhumei; Li, Huiliang; Zhang, Xue-Song; Mao, Xinjun; Li, Ningning; et al. (Frontiers in Microbiology, 2024)
The gut-brain axis is evident in modulating neuropsychiatric diseases including autism spectrum disorder (ASD). Chromosomal 16p11.2 microduplication 16p11.2dp/+ is among the most prevalent genetic copy number variations (CNV) linked with ASD. However, the implications of gut microbiota status underlying the development of ASD-like impairments induced by 16p11.2dp/+ remains unclear. To address this, we initially investigated a mouse model of 16p11.2dp/+, which exhibits social novelty deficit and repetitive behavior characteristic of ASD. Subsequently, we conducted a comparative analysis of the gut microbial community and metabolomic profiles between 16p11.2dp/+ and their wild-type counterparts using 16S rRNA sequencing and liquid chromatography-mass spectrometry (LC/MS). Our microbiota analysis revealed structural dysbiosis in 16p11.2dp/+ mice, characterized by reduced biodiversity and alterations in species abundance, as indicated by α/β-diversity analysis. Specifically, we observed reduced relative abundances of Faecalibaculum and Romboutsia, accompanied by an increase in Turicibacter and Prevotellaceae UCG_001 in 16p11.2dp/+ group. Metabolomic analysis identified 19 significantly altered metabolites and unveiled enriched amino acid metabolism pathways. Notably, a disruption in the predominantly histamine-centered neurotransmitter network was observed in 16p11.2dp/+ mice. Collectively, our findings delineate potential alterations and correlations among the gut microbiota and microbial neurotransmitters in 16p11.2dp/+ mice, providing new insights into the pathogenesis of and treatment for 16p11.2 CNV-associated ASD.